A Three Country Comparative Analysis of Managerial CSR Perspectives: Insights From Lebanon, Syria and Jordan - Jamali, Dima (Journal of business ethics, 2009)
Corporate social responsibility (CSR) is a concept that has acquired a new resonance in the global economy. With the advent of globalization, managers in different contexts have been exposed to the notion of CSR and are being pressured to adopt CSR initiatives. Yet, in view of vastly differing national cultures and institutional realities, mixed orientations to CSR continue to be salient in different contexts, oscillating between the classical perspective which considers CSR as a burden on competitiveness and the modern perspective that views CSR as instrumental for business success. Capitalizing on the two-dimensional CSR model developed by Quazi and O’Brien (Journal of Business Ethics 25, 33–51, 2000), this article assesses managerial perspectives towards CSR in three neighboring Middle Eastern countries (Lebanon, Syria and Jordan) through an empirical study involving 333 managers. The findings lend support to the Quazi and O’Brien model (2000), suggesting some commonalities in CSR orientations as well as minor divergences. The findings are discussed and cross-cultural implications drawn accordingly.